2018
DOI: 10.1016/j.addr.2018.03.007
|View full text |Cite
|
Sign up to set email alerts
|

In situ forming injectable hydrogels for drug delivery and wound repair

Abstract: Hydrogels have been utilized in regenerative applications for many decades because of their biocompatibility and similarity in structure to the native extracellular matrix. Initially, these materials were formed outside of the patient and implanted using invasive surgical techniques. However, advances in synthetic chemistry and materials science have now provided researchers with a library of techniques whereby hydrogel formation can occur in situ upon delivery through standard needles. This provides an avenue… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
428
0
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 676 publications
(429 citation statements)
references
References 152 publications
(169 reference statements)
0
428
0
1
Order By: Relevance
“…Hydrogels are readily suited for biological applications because of their tissue‐like mechanical properties, high water content, biocompatibility, and stimuli‐responsiveness. In the field of drug delivery, hydrogels provide sustained and temporally controlled delivery of drugs in localized regions, reducing off‐target toxicity and increasing clinical efficacy …”
Section: Rheological Properties Of Hpmc:np and Alginate Materialsmentioning
confidence: 99%
See 1 more Smart Citation
“…Hydrogels are readily suited for biological applications because of their tissue‐like mechanical properties, high water content, biocompatibility, and stimuli‐responsiveness. In the field of drug delivery, hydrogels provide sustained and temporally controlled delivery of drugs in localized regions, reducing off‐target toxicity and increasing clinical efficacy …”
Section: Rheological Properties Of Hpmc:np and Alginate Materialsmentioning
confidence: 99%
“…In the field of drug delivery, hydrogels provide sustained and temporally controlled delivery of drugs in localized regions, reducing off-target toxicity and increasing clinical efficacy. [4,[6][7][8][9] Administrating cells through highgauge needles is becoming more common due to the development of cell therapies [10] and 3D bioprinting technologies [3] ; however, previous studies have shown that injecting cells through clinically relevant needles often results in cell death and poor cell viability. [11] Targeted cell delivery is often desired for medical application, but the therapeutic effect of the treatment is decreased because many of the cells injected in saline solutions (i.e., phosphate-buffered saline [PBS]) are regurgitated due to the pressure in the tissue and fluid flow away from the injection site.…”
mentioning
confidence: 99%
“…These materials can furthermore respond to a variety of environmental stimuli with changes in their chemical, biological, mechanical, or macroscale properties . There are multifarious biomedical applications wherein hydrogels are used, including oral drug formulations, injectable drug depots, in situ forming biomaterials, and contact lenses, among many others . For an appreciation of this field, our reader is encouraged to consult many excellent papers and reviews, including those cited here, which offer exhaustive coverage of the synthesis, preparation, characterization, and use of hydrogels for an assortment of biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
“…Localized delivery of stem cells using biomaterials can mitigate these issues . An ideal material should not only enable minimally invasive delivery by injection, and retain cells after transplantation to achieve sustained function, but also create an artificial stem cell niche in situ for higher efficacy and longer maintenance of the therapy . Specifically, the biomaterial should provide suitable biophysical and biochemical microenvironmental cues for enhanced control of cell function in vivo .…”
mentioning
confidence: 99%
“…Specifically, the biomaterial should provide suitable biophysical and biochemical microenvironmental cues for enhanced control of cell function in vivo . However, current injectable biomaterials suffer from ineffective modulation or lack of porosity for mass transport, cell motility, proliferation, cell–cell adhesion, or new tissue formation …”
mentioning
confidence: 99%